Zuhd and Psychological Well-Being: Exploration of the Thought of Sheikh Nawawi al-Bantani - Ihsan, Nur Hadi; Faturrahman, Mochammad Eka (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
Amid the pressure-filled flow of modernity, Sheikh Nawawi al-Bantani's concept of zuhd offers a new perspective on achieving psychological well-being. This study explores the intersection between the teachings of Zuhd al-Bantani and the six dimensions of psychological well-being developed by Ryff. Through qualitative analysis based on the literature study, a positive correlation was found between the concept of zuhd a l-Bantani and increased psychological well-being. The three main components of zuhd - perception of divine support, orientation to the afterlife, and total acceptance of life experiences - play a significant role in building self-acceptance, environmental mastery, and personal growth. Zuhd also encourages forming positive relationships with others and provides a clear purpose in life. This study suggests that the implementation of zuhd can be an effective strategy in dealing with contemporary psychological challenges, offering a balance between spirituality and mental health. These findings pave the way for further integration between classical Sufism teachings and modern psychological approaches, providing a holistic alternative to improve quality of life amidst the complexities of the contemporary world. This study's implications could revolutionise the approach to psychological well-being by integrating classical spiritual wisdom into contemporary mental health practices.